Implementation of the Teams Games Tournament (TGT) Model to Improve Islamic Education Learning Outcomes for SMAN 8 Bekasi Students - Suprima, Suprima; Hasibuan, Akmal Rizki Gunawan; Sari, Ana Yunita; Mulyadi, Acep (Faculty of Education Universitas Negeri Malang, 2023)
This study intends to improve the learning outcomes of Islamic Religious Education with the Teams Games Tournament (TGT) cooperative learning method. The data and subjects of this study were taken from 33 students of class XI IPS 3 at SMA Negeri 8 Bekasi using observation, test, and documentation techniques. The application of the learning method is carried out in 3 cycles. The results of this study prove that the PAI learning outcomes of class XI IPS 3 students of SMAN 8 Bekasi by applying the TGT learning model get an increase. This can be observed in the results of the initial test that was applied before the pre-CAR cycle 1 action, the successful achievement of the KKM score of 75 was obtained for 13 students (40%) with an average score of 67.4. During the first cycle of action, as many as 18 students (54%) with an average score of 73.78 were able to achieve the KKM score. However, the success indicator of the score of 85 has not been achieved by the students, so the researchers continued with cycle 2. In cycle 2, the student learning outcomes increased to 27 students (81%) with an average score of 79.27. In the last 3 cycles, students achieved a minimum standard score when they increased to 33 people or 100% with an average score of 86.69. Through the results of this study, it can be stated that the TGT learning model can improve PAI learning outcomes for students of class XI IPS 4 SMAN 8 BekasiKeywords: Learning Model, Islamic Religious Education, Learning Outcome